The Influence of Digital Advertising, Online Reviews, and Influencer Endorsements on Generation Z’s Purchasing Decisions for Skintific Products on TikTok - Feni Novalia; Setya Indah Isnawati (Golden Ratio of Data in Summary, 2026)
This study aims to determine and analyze the influence of digital advertising features, online reviews, and influencer endorsements on purchasing decisions for Skintific products among Generation Z TikTok users in Bandungan District. The population in this study was Generation Z who lived in Bandungan District who had purchased Skintific products, with a sampling technique using the purposive sampling method . Data were collected through distributing questionnaires via Google Form and analyzed using multiple linear regression analysis methods, normality tests, multicollinearity tests, heteroscedasticity tests, f tests, and t tests . The analysis tool in this study used SPSS Windows ver.27. The results of the study indicate that digital advertising variables have a positive and significant effect on purchasing decisions. Online reviews were also found to have a positive and significant effect on purchasing decisions. However, influencer endorsement variables did not show a positive and significant effect on Generation Z purchasing decisions for Skintific products in Bandungan District. These findings indicate that Generation Z consumers in Bandungan District trust direct advertising content and user testimonials more than promotions from public figures.